Reference values of normal abdominal aortic areas in Chinese population measured by contrast-enhanced computed tomography - Wang, Xiang; Jin, Shasha; Wang, Qing; Liu, Jiawei; Li, Fei; Chu, Haiwei; Zheng, Dexing; Zhang, Xiaolong; Ding, Jianrong; Pan, Jingli; Zhao, Wenjun (Frontiers in Cardiovascular Medicine, 2022)
Objective To generate reference values of the normal areas of the abdominal aorta at various levels among Chinese people and to explore the factors that may promote the expansion of the abdominal aorta. Methods The areas of normal abdominal aortas were gauged at various levels based on inner-to-inner measurements in 1,066 Chinese adult patients (>18 years) without the abdominal aortic disease. The areas of subphrenic abdominal, suprarenal abdominal, infrarenal abdominal, and distal abdominal aortas were measured. The demographic and clinical characteristics were collected into a specifically designed electronic database. Multivariable linear regression was used to analyze the potential risk factors promoting the expansion of the abdominal aorta. Results In males, the median areas of the subphrenic abdominal aorta, suprarenal abdominal aorta, infrarenal abdominal aorta, and distal abdominal aorta were 412.1, 308.0, 242.2, and 202.2 mm2, respectively. In females, the median areas of the subphrenic abdominal aorta, suprarenal abdominal aorta, infrarenal abdominal aorta, and distal abdominal aorta were 327.7, 243.4, 185.4, and 159.6 mm2, respectively. The areas of the abdominal aorta at different levels were larger in males than in females and increased with age. Multiple linear stepwise regression analysis showed that the subphrenic abdominal aortic area was significantly related to age (β = 0.544, p < 0.001), sex (β = 0.359, p < 0.001), and hypertension (β = 0.107, p < 0.001). Suprarenal abdominal aortic area was related to age (β = 0.398, p < 0.001), sex (β = 0.383, p < 0.001), history of smoking (β = 0.074, p = 0.005), and hypertension (β = 0.111, p < 0.001). The infrarenal abdominal aortic area was correlated with age (β = 0.420, p < 0.001), sex (β = 0.407, p < 0.001), and history of smoking (β = 0.055, p = 0.036). The distal abdominal aortic area was correlated with age (β = 0.463, p < 0.001), sex (β = 0.253, p < 0.001), and hypertension (β = 0.073, p = 0.013). Conclusion The abdominal aortic areas at different levels were larger in males than in females. Aging, hypertension, and smoking prompt the expansion of abdominal aorta.